Profile of pre-service civic teachers' TPACK (Technological Pedagogical and Content Knowledge) in basic teaching skills course - Damayanti, Ayu Maya (International Journal for Educational and Vocational Studies)
This study explains and describes pre-service Civic teachers' technological pedagogical content knowledge (TPACK) abilities. The method used in this research is descriptive qualitative. The subjects of this study were the civic pre-service teacher. The data collection instruments used were lesson plans, observation sheets, questionnaires, and interview sheets. Based on the research conducted, positive results were obtained. Students assume that through learning basic teaching skills, students' TPACK abilities increase. From this research, it can also be concluded that further research is needed to determine the factors that influence the TPACK ability of prospective teacher students.